Bifenilos policlorados (PCBs) em pescados in natura do litoral do Rio Grande do Sul, Brasil - Pigatto, Giane Magrini (2013)
Polychlorinated biphenyls (PCBs) are toxic, non-biodegradable, and lipophilic chemical compounds of industrial origin. In Brazil, PCBs are still used in old electrical transformers and capacitors which were installed up to 1981 when their use and commercialization were banned. However, the permission to use devices with PCBs installed up to the early 80s was maintained up to the moment that their dielectric fluids or the entire device be fully replaced for products free of PCBs. Currently, PCBs are classified as persistent organic pollutants (POPs) because they pollute and accumulate in the environment affecting all organisms in the food chain. The main form of human intake is the ingestion of contaminated food, especially food of animal origin. Fish are the main means of transmission of PCB congeners to the human body. The concern about PCBs is centered on their toxicological potential, especially as inducers of cancer. Thus, the aim of this study was to investigate the possible contamination by residues of 11 individual PCB congeners in fresh marine fish from the state of Rio Grande do Sul (RS), Brazil. The methodology for the analysis of PCBs in fish included sampling on the coast of RS, the extraction and purification of these compounds by the use of acidified silica gel and solvents, as well as their identification and quantification using gas chromatography coupled to a micro electron capture detector (GC - μECD). Results were confirmed by gas chromatography coupled to mass spectrometry (GC - MS). PCBs investigated were not found in all samples. PCBs 28 and 52 were not detected. PCBs 153, 138, 180, 118, 101, 77, and 81 were found in 98.33 %, 95%, 93.33%, 60%, 33.33 %, and 31.67 % of the samples, respectively. PCBs 126 and 169 were found at lower frequencies, 18.33% and 15%, respectively. The individual congeners found in higher mean concentrations were PCB 153 (184.36 ng/g fat), followed by PCB 138 (159.27 ng/g fat), PCB 118 (98.16 ng/g fat), PCB 180 (69.04 ng/g fat), PCB 101 (32.99 ng/g fat), and PCB 77 (12.95 ng/g fat). PCBs 81, 126 and 169 were found in lower concentrations (4.97 ng/g, 4.49 ng/g and 2.08 ng/g fat, respectively). Results confirm the contamination by PCBs of all marine species of consumption analyzed and can be used as indicators of environmental contamination by these compounds in the coast of RS.